The Effect of Service Quality, Promotion, and Location on Customer Satisfaction of Bakmi Jawa Pak Ijan Kontjer 2 Mojolaban Districrt Sukoharjo 2022 - Rohwiyati Rohwiyati; Indrian Supheni (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2022)
This study aims to determine the effect of service quality, promotion and location on customer satisfaction Bakmi Jawa Pak Ijan Kontjer 2 either partially or simultaneously. The variables of service quality (X1), promotion (X2), location (X3), and customer satisfaction (Y), were measured using a Likert scale. This research is a quantitative case study. Primary data obtained from interviews and observations. The research population is infinite. The number of samples in this study were 100 customers of Bakmi Jawa Pak Ijan Kontjer 2. The analysis technique used was multiple linear regression test, F test, t test, and coefficient of determination test. The results showed that partially service quality variables (X1), promotion (X2), location (X3) had a significant effect on customer satisfaction (Y). These three variables have a significant effect on employee performance simultaneously.